Catheter-related bloodstream infection caused by Kodamaea ohmeri in China - Chenrui Hou (Elsevier, 2019)
Summary: Kodamaea ohmeri is a rare yeast pathogen that has recently emerged as an important cause of fungaemia in immunocompromised patients. In most cases, identification to the species level requires the adoption of new tools, including matrix-assisted laser desorption/ionization time of flight mass spectrometry (MALDI-TOF-MS) or DNA sequencing. As K. ohmeri is a teleomorph of Candida guilliermondii var. membranaefaciens and its susceptibility to fluconazole is variable, a rapid and accurate identification of this yeast is important. Echinocandins may be the first choice for empiric therapy for this pathogen. We report the case of a 25-year-old male patient from North China who developed a catheter-related bloodstream infection caused by K. ohmeri. He was treated with caspofungin in hospital. He improved after removal of the central venous catheter and use of caspofungin as therapy. The K. ohmeri strain was identified using a MALDI-TOF mass spectrometer and a Vitek 2YST card. Definitive identification was obtained by a sequencing test of the internal transcribed spacer regions of the rDNA. Our patient findings, the first reported in mainland China, highlighted the diagnostic challenges associated with catheter-related bloodstream infection caused by fungi. Keywords: Catheter-related bloodstream infection, Kodamaea ohmeri, Caspofungin, Case report